ASSEMBLY COMPRISING A CIRCUIT BREAKER, A RELAY AND A SYSTEM FOR POSITIONING AND LOCKING THE RELAY IN PLACE ON THE CIRCUIT BREAKER - BLAISE, Bertrand; KETTERER, Olivier; DOGAN, Tolga (2025)
The subject matter of the present invention is a system for positioning and locking a relay (1) in place on a circuit breaker (2), the system being characterized in that it comprises: - on the circuit breaker (2): * a receiving interface (51) configured so as to have a relay connection interface for the relay (1) pass therethrough; * a locking plate (52) parallel to the receiving interface and configured so as to have the relay connection interface and at least one relay fastening interface (9) pass therethrough, and comprising an interface for engagement with the relay fastening interface; and * a translation mechanism (10) for translating the locking plate relative to the receiving interface; - on the relay (1): at least one fastening interface (9) positioned at the end of the relay (1) for engaging with the engagement interface of the translated locking plate.